Theoretical philosophy by I.Kant: on some stereotypes of its explication. - Panafidina, Oksana (Actual Problems of Mind, 2017)
The paper attempts to refute the main stereotypes in the understanding of Kant’s theoretical philosophy. The author claims that it is incorrect to consider Kant among the founders of dialectics as a theory of development and to qualify his doctrine as idealistic.